2022
DOI: 10.3390/toxins14070436
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Complications of Snakebite Envenoming: Case Studies

Abstract: There are an estimated 5.4 million snakebite cases every year. People with snakebite envenoming suffer from severe complications, or even death. Although some review articles cover several topics of snakebite envenoming, a review of the cases regarding cerebral complications, especially rare syndromes, is lacking. Here, we overview 35 cases of snakebite by front-fanged snakes, including Bothrops, Daboia, Cerastes, Deinagkistrodon, Trimeresurus, and Crotalus in the Viperidae family; Bungarus and Naja in the Ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 122 publications
0
5
0
1
Order By: Relevance
“…Towards this end, Feola et al reported 2.6% of patients with cerebrovascular complications among 309 snakebite victims 9. Ischaemic stroke has also been reported in various snake envenomation 16–21. Gawarammana et al found 1.8% ischaemic stroke cases in 500 viper bite patients 22.…”
Section: Discussionmentioning
confidence: 99%
“…Towards this end, Feola et al reported 2.6% of patients with cerebrovascular complications among 309 snakebite victims 9. Ischaemic stroke has also been reported in various snake envenomation 16–21. Gawarammana et al found 1.8% ischaemic stroke cases in 500 viper bite patients 22.…”
Section: Discussionmentioning
confidence: 99%
“…20 Sabe-se ainda que, a depender da gravidade de certas intoxicações, podem-se obter sequelas consideráveis, não sendo possível descartar a possibilidade de que o veneno tenha, de alguma forma, contribuído para alguma agressão cerebral permanente e incomum. 21 Considerando-se os níveis pressóricos aumentados mesmo meses depois do acidente, há de questionar a integridade da saúde vascular em nível sistêmico após o trauma. A título de exemplificação, existe, publicado, um relato de caso indiano que segue esta linha de raciocínio: a ação do veneno vasculotóxico da cobra Daboia russelii em um homem de 42 anos foi suficiente para provocar a síndrome da sela vazia e desencadear transtorno delirante orgânico tipo esquizofrênico.…”
Section: Discussionunclassified
“… 64 Chemical compounds with prothrombotic properties in snake venom, such as snake C-type lectin-like proteins, SVSPs (snake-venom serine proteases), and PLA2 (phospholipase A2), are believed to cause ischaemic stroke and procoagulant metalloproteases and hemorrhaging to lead to consumptive coagulopathy and ICH. 64 , 65 …”
Section: Unique Etiological Mechanisms Of Stroke In the Searmentioning
confidence: 99%